Simulating noisy variational quantum eigensolver with local noise models. Issue 4 (6th September 2021) - Zeng, Jinfeng; Wu, Zipeng; Cao, Chenfeng; Zhang, Chao; Hou, Shi‐Yao; Xu, Pengxiang; Zeng, Bei
Abstract: The variational quantum eigensolver (VQE) is a promising algorithm to demonstrate quantum advantage on near‐term noisy‐intermediate‐scale quantum (NISQ) computers. One central problem of VQE is the effect of noise, especially physical noise, on realistic quantum computers. We systematically study the effect of noise for the VQE algorithm by performing numerical simulations with various local noise models, including amplitude damping, dephasing, and depolarizing noise. We show that the ground state energy will deviate from the exact value as the noise probability increase, and typically, the noise will accumulate as the circuit depth increase. The results suggest that the noisy quantum system can remain entanglement at the noise level of NISQ devices by comparing the VQE solution with the mean‐field solution for the many‐body ground state problem. We build a noise model to capture the noise in a real quantum computer, and the corresponding numerical simulation is consistent with experimental results on IBM Quantum computers through cloud. Our work sheds new light on the practical research of noisy VQE, and the deep understanding of the noise effect of VQE will also help develop error mitigation techniques on near‐term quantum computers.